Automation of Large Low-Volume Products: A feasibility and concept study on automated welding of hauler body wear plates - Vertetics, Oskar; Wingårdh, Theodor (My University, 2022)
This master’s thesis deals with the conceptual development of a production concept for automated welding of hauler body wear plates at Volvo Construction Equipment in Braås. There is a need to investigate and emphasize the potential for possible future adoptions of automated and flexible welding systems, for improved production efficiency and a better work environment. Interviews, observations, and literature studies were carried out to map the current state and identify the needs and scope. The needs and scope formed the foundation of the concept development process, which included rigorous concept gen eration, evaluation, and selection processes. Relevant areas and problems were further analysed and investigated to assess the technical base, test the validity of alternatives, and quantify unknowns and weaknesses. A final and indicative production concept was compiled concerning robotics and a workpiece positioner. Mainly, the production concept enables efficient, flexible, and autonomous robot welding of hauler body wear plates, sig nificantly reducing the manual labour of welding wear plates. Furthermore, the presented production concept also provides a better and safer working environment, increased pro duction capacity, reduced TTM, reduced risk of MSDs, increased production system flex ibility, and minimisation of material handling losses.
Keywords: welding, GMAW, autonomous, positioner, robot cell, system design, manufacturing, flexible